Interactions between self-help and hospice and palliative care – Opportunities, barriers and needs (Self-Pall): A study protocol - Saskia Kauzner; Manuela Schneider; Julia Berendt; Christoph Ostgathe; Maria Heckel (PLoS ONE, 2026)
Introduction A progressive and life-limiting disease can cause enormous psychological distress for patients and family caregivers. Health-related collective self-help could be a coping strategy by facilitating interaction with others in similar situations. Scarce literature is available on how those patients and their caregivers could benefit from self-help activities, how self-help groups deal with death and grief, and whether there are interactions between self-help and hospice and palliative care. The Self-Pall project aims at developing recommendations tailored at different actor groups to support the interactions between self-help and hospice and palliative care. Methods We will use a qualitative, multi-method, sequential research design. The project started in 07/2025 and will end in 06/2027. Semi-structured interviews will be conducted with patients, family caregivers, and representatives of hospice and palliative care and of self-help to explore personal and professional experiences focussed on opportunities, barriers, and needs. A draft of recommendations will be derived, which will then be confirmed and expanded upon within focus groups. A representative expert panel will refine and agree upon the recommendations through an iterative, multi-level Delphi process. The engagement of a Patient and Public Involvement group will ensure the relevance of our research to the public and provide transparency. Discussion We will explore awareness, needs, and factors that promote or hinder self-help activities from the perspective of patients, caregivers, and professionals. From a self-help perspective, we will assess how to deal with dying, death, and grief, as well as knowledge and use of hospice and palliative care services, any barriers and how to overcome them. We are the first to explore interactions between self-help and hospice and palliative care bilaterally to develop practical recommendations and key principles with significant implications for practice.